Potential Use of Morphological Characteristics in Evaluating Natural Variation of “Barako” Seedlings - Aguilar, Julienne Davis V. (Animo Repository, 2021)
The Philippines is one of only three countries able to produce Coffea liberica and grow two other species of coffee, Coffea canephora, Coffea arabica. Coffea liberica, or “Barako,” is the least cultivated of coffee species. Its unique taste has high potential to grow in the market if production was increased. However, the 2020 Taal Volcano eruption resulted in thousands of damaged Barako trees in 2020 and 2021. As new seedlings are produced, the question of variety among planting material comes up. Farmers need a method to evaluate natural differences of current Barako trees, to answer whether seedlings from farms cultivating Barako are naturally different. This research aims to determine if the morphological characteristics of cultivated seedlings from different farms can be classified through image and statistical analysis. Basic knowledge on how varieties―which producedifferent flavors, aroma, and market value of coffee―differ among farms is needed for a strategy to increase the number of seedlings. This study’s initial data set indicated statistically significant differences in the average seedling height per node and the leaf area per length of 31, 10-month old coffee seedlings from two different farms, grown in a common environment. The process may be developed further for use in evaluating natural variation among C. liberica as seedlings.